Pengetahuan Pegawai terhadap Kinerja Keuangan Pemerintah Daerah dengan Perkembangan Teknologi Informasi sebagai Pemoderasi - Hurian Kamela (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the effect of employee knowledge on local government financial performance, with the development of information technology as a moderating variable. The research background is based on the importance of human resource competencies in managing public finances in an accountable and transparent manner, especially in the era of digitalization of government administration. This study employs a quantitative approach, utilizing a survey method among local government employees in several administrative regions. Data were collected through questionnaires and analyzed using moderation regression techniques to test the relationship between variables. The results showed that employee knowledge has a positive and significant effect on local government financial performance. Additionally, the development of information technology has been proven to strengthen relationships, as the use of financial information systems enables employees to manage and report finances more effectively and efficiently. These findings suggest that enhancing the quality of human resources requires the development of adequate digital infrastructure, enabling optimal improvement in local financial performance. This research provides important implications for policymakers in designing training strategies and digitizing public sector financial management.